Applying Social Exchange Theory to Value Co-Creation Frame: Does it Leads to Customer Loyalty? - Adinda Farhana (Faculty of Economics, Universitas Sriwijaya, 2021)
The emergence of E-commerce has brought many advantages, especially in economic development. With the increasing number of E-commerce users, it is crucial for e-commerce platforms to sustain their business. Applying value co-creation is beneficial for e-commerce to gain a competitive advantage that leads to customer loyalty. This study aims to seek the correlation between key constructs in Social Exchange Theory which is satisfaction and trust with value co-creation behaviour. Further, this study also investigates whether the value co-creation behaviour leads to customer’s loyalty.The research uses SEM-PLS to examine the model, and the result indicates value co-creation behavior that consists of participation behavior and citizenship behavior influences customer loyalty positively. Hence, the e-commerce platform needs to gain customer trust and satisfaction to enhance customer willingness to value co-creation behavior, leading to customer loyalty.